SISTEM INFORMASI UNIT KEGIATAN MAHASISWA (UKM) DI UNIVERSITAS MUHAMMADIYAH PAREPARE - Almauna, Elawati; Suwardoyo, Untung; Marlina; Masnur (Jurnal Manajemen dan Teknologi Informasi, 2025)
This study aims to evaluate the effectiveness of the information system implemented in the Student Activity Unit (UKM) of the University of Muhammadiyah Parepare in supporting student management and participation. This information system is designed to facilitate access to information, registration, and administration of UKM activities. The method used in this study is a descriptive quantitative approach with a survey, where data is collected through questionnaires distributed to active students registered as UKM members. The variables analyzed include information needs, ease of use, system performance, and user satisfaction. The results showed that the majority of respondents were satisfied with the ease of access to information and use of the system. However, there are several areas that need improvement, especially related to the speed of system access and the system's ability to handle large data loads. In addition, the information provided needs to be clearer and more complete, especially regarding UKM profiles and registration procedures. This study suggests developing a system to improve performance, such as optimizing access time and larger data handling capacity. Improved search and filter features are also needed to improve the efficiency of system use. This study is expected to contribute to the development of UKM information systems in higher education and provide recommendations for system managers on other campuses.